2007
DOI: 10.1080/13693780601186069
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of canine histoplasmosis in Japan

Abstract: A recent case of canine histoplasmosis, the first confirmed case of disseminated infection accompanied by carcinoma in Japan, was diagnosed by clinical characteristics, histopathological examination, chest radiographs, ocular fundoscopy and molecular biological data. The clinical manifestations were not limited to cutaneous symptoms but were referable to disseminated infection, similar to human autochthonous cases. The partial sequences of the internal transcribed spacer (ITS1/2) regions of the ribosomal DNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…capsulatum var. farciminosum, with clinical cases being reported in dogs (23), badgers (24), and even humans (25). The phylogeny of Histoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…capsulatum var. farciminosum, with clinical cases being reported in dogs (23), badgers (24), and even humans (25). The phylogeny of Histoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogeny of Histoplasma spp. has been examined using a range of different gene loci (22, 23, 2530). As has been frequently reported for fungi, sequence variation in the internal transcribed spacer (ITS) region of the rRNA operon provides a resolving power sufficient to discriminate between closely related species and variants and can contribute to the design of specific PCR-based detection protocols (25, 27, 31, 32).…”
Section: Introductionmentioning
confidence: 99%
“…Seven cases of canine histoplasmosis have been reported in Japan [12,17,18,20,22]. In addition, Murata et al have compared canine cases with worldwide human and equine cases with respect to partial sequences on the internal transcribed spacer (ITS1/ 2) regions of the ribosomal DNA genes [17]. This phylogenetic analysis performed by nested polymerase chain reaction (nested PCR) and sequence analysis have revealed that these canine cases in Japan were closely related to the Asian autochthonous human cases.…”
mentioning
confidence: 99%
“…Recently, however, autochthonous cases have been reported in humans [13]. Seven cases of canine histoplasmosis have been reported in Japan [12,17,18,20,22]. In addition, Murata et al have compared canine cases with worldwide human and equine cases with respect to partial sequences on the internal transcribed spacer (ITS1/ 2) regions of the ribosomal DNA genes [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation